Building belief, achieving balance: how organizational climate fosters self-efficacy for a fulfilling work–life - Ishret Fayaz; Farzana Gulzar (IIM Ranchi Journal of Management Studies)
Purpose – This study investigates how the organizational climate influences work–life balance (WLB) among women employees in universities across Jammu and Kashmir, with a focus on the mediating role of self-efficacy. Design/methodology/approach – Adopting a quantitative research design, this study utilized a survey methodology to collect data from women employees in 11 universities within Jammu and Kashmir. The study analyzed responses from 587 participants through partial least squares structural equation modeling (PLS-SEM) using SmartPLS 4.0. Findings – The findings underscore the significant positive impacts of organizational climate dimensions – autonomy, integration, involvement, support, training and welfare – on work–life balance. Self-efficacy was found to partially mediate the relationships between organizational climate dimensions and work–life balance, underscoring its role in enhancing employees’ capacity to manage work and personal life. The study highlights the importance of a supportive organizational climate in fostering self-efficacy and, subsequently, achieving a satisfactory work–life balance among women employees in academic settings. Originality/value – This research contributes to the existing literature by exploring the nuanced relationship between organizational climate, self-efficacy and work–life balance, specifically among women employees in the educational sector of Jammu and Kashmir. By highlighting self-efficacy as a critical mediator, the study offers novel insights into the mechanisms through which organizational climate affects work–life balance, providing valuable implications for policy and practice in educational institutions.